ChemInform Abstract: "Base Effect" in the Auto‐Tandem Palladium‐Catalyzed Synthesis of Amino‐Substituted 1‐Methyl‐1H‐α‐carbolines. Issue 26 (6th June 2013) - Yadav, Ashok K.; Verbeeck, Stefan; Hostyn, Steven; Franck, Philippe; Sergeyev, Sergey; Maes, Bert U. W.
Abstract A regioselective auto‐tandem Pd‐catalyzed process consisting of intramolecular direct arylation and a consecutive intermolecular Buchwald‐Hartwig reaction is developed.